Exploring an increased role for Australian community pharmacy in mental health professional service delivery: evaluation of the literature - Hattingh, H. Laetitia; Scahill, S.; Fowler, J.; Wheeler, A. (2015)
Background: Australian general practitioners primarily treat mental health problems by prescribing medication dispensed by community pharmacists. Pharmacists therefore have regular interactions with mental health consumers and carers.Aims: This narrative review explored the potential role of community pharmacy in mental health services.Method: Medline, CINAHL, ProQuest, Emerald, PsycINFO, Science Direct, PubMed, Web of Knowledge and IPA were utilised. The Cochrane Library as well as grey literature and “lay” search engines such as GoogleScholar were also searched.Results: Four systematic reviews and ten community pharmacy randomised controlled trials were identified. Various relevant reviews outlining the impact of community pharmacy based disease state or medicines management services were also identified.Conclusion: International studies involving professional service interventions for mental health consumers could be contextualised for the Australian setting. Australian studies of pharmacy professional services for chronic physical health conditions provided further guidance for the expansion of community pharmacy mental health professional services.